Association of Fc receptor-like 5 (FCRL5) with Graves' disease is secondary to the effect of FCRL3. - Simmonds, M; Brand, O; Barrett, J; Newby, P; Franklyn, J; Gough, S (2010)
OBJECTIVE: The Fc receptor-like 3 (FCRL3) molecule, involved in controlling B-cell signalling, may contribute to the autoimmune disease process. Recently, a genome-wide screen detected association of neighbouring gene FCRL5 with Graves' disease (GD). To determine whether FCRL5 represents a further independent B-cell signalling GD susceptibility loci, we screened 12 tag SNPs, capturing all known common variation within FCRL5, in 5192 UK Caucasian GD index cases and controls. DESIGN: A case-control association study investigating twelve tag SNPs within FCRL5 which captured the majority of known common variation within this gene region. PATIENTS: A data set comprising 2504 UK Caucasian patients with GD and 2688 geographically matched controls taken from the 1958 British Birth cohort. MEASUREMENTS: We used the chi-squared test and haplotype analysis to investigate the association between the tag SNPs and GD before performing logistic regression analysis to determine whether association at FCRL5 was independent of the known FCRL3 association. RESULTS: Three of the FCRL5 tag SNPs, rs6667109, rs3811035 and rs6692977 showed association with GD (P = 0·015-0·001, OR = 1·15-1·16). Logistic regression performed on all FCRL5 and, previously screened, FCRL3 tag SNPs revealed that association with FCRL5 was secondary to linkage disequilibrium with the FCRL3, rs11264798 and rs10489678 SNPs. CONCLUSIONS: FCRL5 does not appear to be exerting an independent effect on the development of GD in the UK. Fine mapping of the entire FCRL region is required to determine the exact location of the aetiological variant/s present.